Secondary Trigeminal Neuralgia after a Brainstem Hemorrhagic Stroke with Adverse Reaction to Carbamazepine: A Case Report - I Gusti Agung Ayu Andra Yusari; Ida Ayu Sri Wijayanti; Ketut Widyastuti; I Made Oka Adnyana (Bali Journal of Anesthesiology)
Secondary trigeminal neuralgia (TN) is a rare manifestation of neuropathic pain in post-stroke patients, which is characterized by paroxysmal unilateral pain in the trigeminal nerve distribution, especially in strokes that occur in the brainstem. We present a case of a female patient, 28 years old, with attacks of right-sided severe pain in the face, which felt like burning and electric shock. The pain began after hospitalization due to a brainstem hemorrhagic stroke in the right pons and mesencephalon, and the pain persisted for several months. She was diagnosed with secondary TN associated with brainstem hemorrhagic stroke. She experienced severe adverse reactions with the first-line pharmacological therapy, carbamazepine and gabapentin. Fluoxetine was given as an alternative therapy, and the patient began to experience improvement in the pain intensity and frequency within a few weeks. Secondary TN is a complication of hemorrhagic stroke in the brainstem, the site of the trigeminal nerve somatosensory component. Management of secondary TN after stroke has its own challenges in selecting the best medication to achieve remission of symptoms, especially when there is an adverse reaction to the first-line treatments, in this case to anticonvulsants. Antidepressants, such as fluoxetine, can be the treatment of choice to improve the symptoms of TN patients in such cases.